(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
For sustainable development and protection of environment, plastic reuse is the best alternative for plastic waste management. Over the years extensive research has been carried out on the use of plastic in civil constructions. Also, the main challenges in the construction sector are caused by the Portland cement production. The obvious, basic and suitable solution is the less consumption of the same and by partial replacement of cement by SCMs (supplementary cementitious materials). Though utilization of plastic waste, fly ash, rice husk ash, silica fume and reduction in cement usage is advantageous from environmental point of view but their properties and behavior together as a construction material requires extensive investigation.In this study, keeping in view the environmental effects caused by the plastic wastes, cement production, various industrial and agricultural wastes; an investigation has been carried out to study the effect of partial replacement of cement by three different wastes i.e., Silica Fume, Fly Ash and Rice Husk Ash in combined proportions along with partial coarse aggregate replacement with plastic waste and to obtain optimum proportions of waste replacement. The research is carried out in two stages. In the first stage only the binder/cement is focused upon and replaced by different percentages in combined proportions of SF, FA and RHA. It was found out that the optimum percentage of cement replacement is 40% in which combined proportion is (10%SF, 10%RHA, 20%FA). In the second stage, the (10%SF, 10%RHA, 20%FA) replacement of cement is kept constant and the natural coarse aggregate is replaced by PP Plastic in proportions 20%, 30% and 40% respectively. Consequently, the optimum proportion of plastic was found to be 20% for the cement replaced plastic induced concrete (CRPIC). Physical characteristics of this cement replaced plastic induced concrete (CRPIC) were determined by compressive strength tests, flexural tests, slump test. The chemical and water absorption properties along with weight of hardened concrete was assessed and the latter was compared with traditional concrete. This research, in general, will decrease the amount of natural coarse aggregate and cement quantity that are used in the construction industry and will consequently reduce the waste that is disposed into the surroundings.